Tradisi Syawalan di Kaliwungu Kendal: Kajian Filosofis Terhadap Nilai Religius dan Sosial - Ifana Ayu Zahrani; Heniza Listiana Amara Putri; Mukhamad Rikza Chamami (Indo Publishing, 2026)
This study examines the Syawalan tradition in Kaliwungu, Kendal Regency, Central Java, an annual tradition commemorating the Haul Kyai Asyari, held seven days after Eid al-Fitr. This study aims to describe the implementation of the Syawalan tradition and analyze the religious values, social values, and philosophical meanings contained within. The method used is descriptive qualitative through in-depth interviews with community leaders and residents of Kaliwungu, as well as direct observation in the field. The results show that Syawalan contains religious values ​​such as strengthening faith, mutual forgiveness, and respect for religious scholars. From a social perspective, this tradition strengthens friendship and the spirit of mutual cooperation among residents. Philosophically, Syawalan reflects the balance between the relationship between humans and God (habluminallah) and the relationship between humans and others (habluminannas), which is in line with the concept of falah in Islam. Despite facing the challenges of modernization, the Kaliwungu community continues to strive to preserve this tradition through education, social media, and support from the local government.